Experimental study on temperature change caused by ScCO2 adsorption–desorption during carbon sequestration in deep coal seam. (1st May 2023) - Yao, Hongbo; Chen, Yuedu; Liang, Weiguo; Song, Xiaoxia
Highlights: The coal mass temperature (CMT) change in the anthracite and bituminous coal during ScCO2 adsorption–desorption under different equilibrium temperatures (ET) and injection pressures are measured. The desorption hysteresis phenomenon (DHP) of ScCO2 is investigated at different ET and quantified by the improved hysteresis index (IHI). A theoretical model is established to describe the influence of adsorption pressure on the CMT change induced by ScCO2 adsorption and desorption. Abstract: Understanding the thermal effect of the coal induced by supercritical CO2 (ScCO2 ) adsorption and desorption is vital in evaluating the heat transfer behaviour during CO2 sequestration in deep coal seams. Therefore, the coal mass temperature (CMT) changes in anthracite and bituminous coal during ScCO2 adsorption–desorption under equilibrium temperature (ET) of 40 °C to 70 °C and maximum adsorption pressures of 12 MPa, were investigated experimentally. The Fourier-transform infrared spectroscopy (FTIR) method measures the functional groups of coal to reveal the mechanism behind the CMT change. The results indicate that the adsorption and desorption of CO2 increase and decrease the coal's temperature, respectively. The induced CMT variation depends on the coal rank, CO2 pressure, and ET. The higher the coal rank, the higher the adsorption pressure; the lower the ET, and the greater the CMT change. At different ET, the CMT variation during adsorption is higher than in desorption, because of the desorption hysteresis phenomenon (DHP). An improved hysteresis index (IHI) was used to quantify this phenomenon. The IHI decreases linearly with the ET, and the value of anthracite is higher than that of bituminous coal. The DHP of ScCO2 during adsorption and desorption is correlated with the induced variation in the coal's functional groups. With the increase in ET, the hydroxyl and oxygen-containing functional groups' contents in coal decrease after ScCO2 adsorption and desorption, reducing the adsorption capacity and weakening the desorption hysteresis effect. A theoretical model was established to describe the influence of adsorption pressure on the CMT change induced by ScCO2 adsorption–desorption. The calculated data are consistent with the experimental data, and the results are meaningful to the ScCO2 sequestration in deep coal seams.